2007
DOI: 10.1002/app.25707
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte complexes formed by hyperbranched poly(sulfone‐amine) hydrochlorate and poly(sodium acrylate)

Abstract: A new type of polyelectrolyte complexes formed by hyperbranched poly(sulfone-amine) hydrochlorate and poly(sodium acrylate) has been reported. It has been found that the stoichiometry between polycation and polyanion is 1.16, which means that hyperbranched polyelectrolyte can also form the compact complexes in spite of the ill-defined structure. Moreover, the effect of various parameters, such as the architecture of poly(sulfone-amine), molecular weight of polymer, concentration and low molecular salt, on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It was found that the polyanion chain length significantly affected the LbL process and that, at lower molecular weights, the adsorbing protein molecule effectively competed with the adsorbed protein for the polyanion. A few years later, Zhou et al 466 reported the fabrication of polyelectrolyte complexes by hyperbranched poly(sulfone amine) hydrochlorate (HPSA-HCl) and sodium polyacrylate (NaPA). They found that the branched structure of HSPA-HCl could form stoichiometric polyelectrolyte complexes with the linear NaPA and had little influence on the complexation behavior.…”
Section: Effect Of Polyelectrolyte Chainmentioning
confidence: 99%
“…It was found that the polyanion chain length significantly affected the LbL process and that, at lower molecular weights, the adsorbing protein molecule effectively competed with the adsorbed protein for the polyanion. A few years later, Zhou et al 466 reported the fabrication of polyelectrolyte complexes by hyperbranched poly(sulfone amine) hydrochlorate (HPSA-HCl) and sodium polyacrylate (NaPA). They found that the branched structure of HSPA-HCl could form stoichiometric polyelectrolyte complexes with the linear NaPA and had little influence on the complexation behavior.…”
Section: Effect Of Polyelectrolyte Chainmentioning
confidence: 99%
“…The sequential layer-by-layer (LbL) deposition of oppositely charged polyelectrolytes on a solid substrate can generate a polyelectrolyte multilayer (PEM). Because of the potential applications of PEMs in various fields, the growth of PEMs has been investigated extensively . In general, the formation of a PEM is influenced not only by solvent quality, temperature, , pH, ionic strength, , charge density, and molecular weight, but also by chain architecture. , Recent studies have shown that PEMs fabricated by star–linear or star–star polyelectrolyte pair exhibit distinct behaviors compared with their linear–linear counterpart in terms of the manner of growth or the post-treatment of multilayers. …”
Section: Introductionmentioning
confidence: 99%